A study of bilayer phosphorene stability under MoS2-passivation. (5th May 2017) - Son, Youngwoo; Kozawa, Daichi; Liu, Albert Tianxiang; Koman, Volodymyr B; Wang, Qing Hua; Strano, Michael S
Abstract: Despite the unique properties of black phosphorus (BP) and phosphorene, including high carrier mobility and in-plane anisotropy, their stability has been hampered by significant crystal deterioration upon exposure to oxygen and water. Herein, we investigate the chemical stability of MoS2 -passivated black phosphorus (BP) or bilayer (2L) phosphorene van der Waals (vdW) heterostructures using the field-effect transistor (FET) and phototransistor effects, measuring the persistence of conductivity and carrier mobility upon atmospheric exposure. Four thicknesses of MoS2 -passivated BP FETs were studied at 1.5 (assigned to bilayer), 5, 13, and 20 nm to elucidate the effects of the MoS2 passivation layer on the device stability and electrical characteristics under dark and illumination (wavelength, λ   =  600 nm) conditions. We find that trilayer MoS2 passivation enhances the photoresponse of a 2L-phosphorene optoelectronic heterojunction by 78% without gate bias. When in contact with a trilayer MoS2 layer, the photoluminescence quantum yield of the phosphorene bilayer crystal apparently decreases 29%. This can be attributed to the difference in absorption in the BP layer induced by the interference color effect generated by the presence of the thin MoS2 layer as well as a built-in electric field that forms at the BP-MoS2 p-n interface helps to dissociate photo-generated electron–hole pairs, thereby reducing the probability of the recombination events. The effectiveness of a trilayer MoS2 as a vdW protection layer is tested by exposing BP-MoS2 vdW vertical heterostructures to the ambient environment for up to 3 weeks as well as annealing at high temperature (350 °C) in an inert Ar environment. We find that the MoS2 passivation layer reduces the dark current of bilayer phosphorene, but this effect decreases with thickness. Thus, we find that 2D MoS2 thin passivation layers provide specific chemical stability and electro-optical enhancement for transparent, flexible BP electronic and optoelectronic devices by acting not only as an atomically thin passivation layer, but also enhancing the photoresponse.